2009
DOI: 10.1177/1076029609342092
|View full text |Cite
|
Sign up to set email alerts
|

Early Stent Thrombosis in Patients Undergoing Primary Coronary Stenting for Acute Myocardial Infarction: Incidence, a Simple Risk Score, and Prognosis

Abstract: Early ST after primary coronary stenting in AMI is strongly related with increased long-term cardiovascular mortality. Premature clopidogrel therapy discontinuation is the most powerful predictor of early ST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
12
1
Order By: Relevance
“…Figures 2 and 3 show the risk of mortality and MACE considering unadjusted and adjusted results separately. Eight of the 10 studies reported crude mortality rate 6,10,14,[16][17][18][19]21 which was 13% in patients experiencing a gastrointestinal bleed (96/738) and 3% in the remaining cohort (1898/55 771). There was a significant risk of mortality with gastrointestinal bleeding …”
Section: Access and Non-access Site Bleedingmentioning
confidence: 99%
See 2 more Smart Citations
“…Figures 2 and 3 show the risk of mortality and MACE considering unadjusted and adjusted results separately. Eight of the 10 studies reported crude mortality rate 6,10,14,[16][17][18][19]21 which was 13% in patients experiencing a gastrointestinal bleed (96/738) and 3% in the remaining cohort (1898/55 771). There was a significant risk of mortality with gastrointestinal bleeding …”
Section: Access and Non-access Site Bleedingmentioning
confidence: 99%
“…We retrieved 25 relevant studies of patients that underwent PCI (total number of subjects 2 400 645), which evaluated the risk of adverse events with and without major bleeding. 2,[4][5][6][7][8][9][10][11][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Excluded studies are shown in Table II in the Data Supplement. The patient cohort size ranged from 73 to 1 216 759, and 106 490 major bleeding events were recorded (23 studies, 4.5%).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of noncoronary clinical factors such as DM [17][18][19], creatinine level on admission [2], and baseline white blood cell [20] and platelet [21] counts were associated with ST. In our study, none of these variables were found to be independent predictors of acute ST, except baseline Mg level ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main concerns remaining with stenting of the patients with acute myocardial infarction (AMI) is the development of stent thrombosis (ST). ST is an uncommon but serious complication that almost always presents as death or a large nonfatal myocardial infarction, usually with ST elevation [2]. It has been reported that there is a persistent and increased risk of early ST in patients with moderate-risk to high-risk acute coronary syndromes, irrespective of the implanted stent type [3].…”
Section: Introductionmentioning
confidence: 99%